Senescent endothelial cells: key commanders of the cellular communication network within atherosclerotic plaques - Xie, Fujia; Xi, Cheng; Bao, Guoqing; Yang, Bin; Zheng, Xiaoyu; Fu, Bowen; Zheng, Zhibin (Frontiers in Immunology, 2026)
Endothelial cell senescence, once considered a passive manifestation of vascular aging, is now recognized as an active driver of atherosclerosis. Senescent endothelial cells (sECs) exhibit distinct morphological and molecular hallmarks, including irreversible growth arrest, altered chromatin structure, and secretion of a pro-inflammatory senescence-associated secretory phenotype (SASP). Through SASP factors, extracellular vesicles, and paracrine signaling, sECs orchestrate a pathological communication network that recruits immune cells, reprograms vascular smooth muscle cells, and compromises endothelial integrity, collectively promoting plaque growth and instability. Central signaling pathways such as the p53/p21 and p16/Rb axes establish the senescent state, while mTOR, NF-κB, and cGAS-STING pathways sustain SASP production. We propose the retinol-binding protein 4 (RBP4) axis as a compelling theoretical framework linking metabolic dysfunction to endothelial senescence. While the TLR4-mediated inflammatory pathway is established, we posit a convergent STRA6-mediated axis that may integrate systemic metabolic stress with local vascular inflammation. Recognizing sECs as “commanders” of the atherosclerotic microenvironment highlights their potential as therapeutic targets. Strategies including senolytics, senomorphics, and upstream pathway inhibition offer promising avenues for attenuating vascular aging. Crucially, our analysis emphasizes the necessity of sex-specific therapeutic approaches, distinguishing between inflamm-aging driven pathologies in men and mechanisms centered on metabolic resilience in women.